Students and teachers’ reasons for using the first language within the foreign language classroom (french and english) in central mexico (2011)
The present study explores the use of the first language in a context of foreign language teaching. This qualitative research presents the classroom practice and points of view of French and English teachers and students within a public educational institute in central Mexico using the techniques of questionnaires and semi-structured interviews. The results show that teachers and the majority of students perceive the use of the first language as positive and part of the teaching and learning process. A small number of students do not like the use of the first language in the classroom and prefer that their teachers use the target language only. La presente investigación explora el uso de la lengua materna en un contexto de enseñanza de lenguas extranjeras. Esta investigación cualitativa presenta la práctica docente y los puntos de vista de maestros y alumnos de francés e inglés en el contexto de una universidad pública del centro de México, mediante el uso de las técnicas del cuestionario y la entrevista semiestructurada. Los resultados muestran que tanto los maestros como la mayoría de los alumnos perciben el uso de la lengua materna como algo positivo en el proceso de enseñanza-aprendizaje. Un número reducido de estudiantes rechaza el uso de la lengua materna y prefiere que su clase de lengua extranjera sea dirigida exclusivamente en la lengua meta. Palabras clave: investigación cualitativa, puntos de vista de alumnos y maestros, uso de la lengua materna.